Evaluasi Penerapan Standar Akuntansi Pemerintah Berbasis Akrual Dalam Penyajian Laporan Keuangan DIPA DITJEN BIMAS KRISTEN Pada Kantor Kementrian Agama Kabupaten Ende - Lomi, Yohana Audivista; Londa, Yulita; Thalib, Sabra B (Jurnal Riset Ilmu Akuntansi, 2021)
The purpose of this study was conducted to determine the application of accrual-based government accounting standards in the presentation of financial reports at the Ministry of Religion Office of Ende Regency, especially in DIPA DITJEN BIMAS KRISTEN. The method in this research uses descriptive qualitative research, to determine the application of accrual-based government accounting in the Ministry of Religion Office of Ende Regency, especially in DIPA DITJEN Bimas Kristen. Data sources are primary data and secondary data. Data collection techniques in this study were observation, interviews, and documentation. From the results of the research conducted, in the DIPA DITJEN Bimas Kristen Office of the Ministry of Religion, Ende Regency, it is known that accrual-based government accounting standards have been understood in theory but to implement them in the field is still very complex because it requires Human Resources who really understand how SAP works itself.